2005
DOI: 10.1016/j.jcat.2005.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotalcites supported on carbon nanofibers as solid base catalysts for the synthesis of MIBK

Abstract: Mechanically strong carbon nanofiber spheres of millimeter size were grown from methane over a preshaped Ni/SiO 2 catalyst. Mg-Al hydrotalcites (HTs) were precipitated in the porous carbon bodies by consecutive impregnation of the reactants and an aging step. In a single sequence, HT loadings as high as 16 wt% were obtained. HTs turned out to be present as platelets with a lateral size of ∼20 nm supported on the carbon nanofibers. After activation by heat treatment and subsequent rehydration, a high number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Various methods have been explored to overcome these problems, such as the combination of LDH with carbon nanofibers [14] and carbon nanotubes [15][16][17][18][19][20], as previously studied in our group [21]. Among the nanocarbons, the 2D geometry of graphene oxide (GO) is obviously compatible with the layered structure of LDHs and there is also a charge compatibility between the positively charged LDH and negatively charged GO.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been explored to overcome these problems, such as the combination of LDH with carbon nanofibers [14] and carbon nanotubes [15][16][17][18][19][20], as previously studied in our group [21]. Among the nanocarbons, the 2D geometry of graphene oxide (GO) is obviously compatible with the layered structure of LDHs and there is also a charge compatibility between the positively charged LDH and negatively charged GO.…”
Section: Introductionmentioning
confidence: 99%
“…As a catalyst support, CHT can be used for nitrous oxide decomposition [28], MIBK synthesis [29], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations reported in literature showed that the actual active basic sites in activated HTs are situated at the edges of the platelets and that the number of these sites can be varied by changing the lateral platelet size [38,40,41,45,46]. A linear correlation between the number of active sites and the activity in the condensation of acetone at 273 K was found [38,40,46].…”
Section: Condensation and Dehydration Over Activated Htsmentioning
confidence: 70%
“…A linear correlation between the number of active sites and the activity in the condensation of acetone at 273 K was found [38,40,46]. We investigated whether a similar structure-activity relationship could be derived for the dehydration reaction as the dehydration reaction is also catalyzed by basic sites [1].…”
Section: Condensation and Dehydration Over Activated Htsmentioning
confidence: 99%